Isolated orbital myocysticercosis in a Muslim boy - Thakur, Anita; Agarwal, Ruchika; Jain, A. M.; Saxena, Nutan (International Journal of Research in Medical Sciences, 2017)
Orbital cysticercosis is secondary to an infestation by Cysticercus cellulosae, the larval form of Taenia solium. We report a case of isolated orbital myocysticersosis in a four year old non pork eater boy who presented with sign and symptoms suggestive of mass lesion in superior orbit. He was managed with medical line of treatment and showed complete resolution of his symptoms. It becomes important to report this case because of unusual site of the cyst, young age of the patient and to highlight the importance of proper sanitary measures in preventing this disease.